2021
DOI: 10.1029/2020gb006694
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Riverine Concentration‐Discharge Relationships by Changes in the Shape of the Water Transit Time Distribution

Abstract: The concentrations of weathering-derived solutes in rivers and their covariance with discharge are thought to reflect reactive-transport processes in hillslopes and to reveal the sensitivity of solute fluxes to climatic change. It is expected that discharge-driven changes in water transit times play some role in setting concentration-discharge (C-Q) relationships, but knowledge gaps remain. To explore the specific role of changes in the shape of the transit time distribution with discharge, we combine models t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 113 publications
1
15
0
Order By: Relevance
“…Low VC stratifies the flows via different depths, leading to distinct chemistry in older waters in deeper zones and in younger waters in shallow soils (Jin et al., 2014; Richardson et al., 2020; Sullivan et al., 2016). Large shallow and deep water contrast and non‐chemostatic (dilution and flushing) patterns in these hillslopes suggest that chemical heterogeneity is required for non‐chemostatic patterns, which is similarly observed in other studies (Torres & Baronas, 2021). This may appear surprising but align with reactive transport principles: Concentration gradients do develop even in idealized, homogeneous systems, as water continues to interact with minerals and dissolve out solutes along its flow paths, although mineral heterogeneity may intensify concentration gradients.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Low VC stratifies the flows via different depths, leading to distinct chemistry in older waters in deeper zones and in younger waters in shallow soils (Jin et al., 2014; Richardson et al., 2020; Sullivan et al., 2016). Large shallow and deep water contrast and non‐chemostatic (dilution and flushing) patterns in these hillslopes suggest that chemical heterogeneity is required for non‐chemostatic patterns, which is similarly observed in other studies (Torres & Baronas, 2021). This may appear surprising but align with reactive transport principles: Concentration gradients do develop even in idealized, homogeneous systems, as water continues to interact with minerals and dissolve out solutes along its flow paths, although mineral heterogeneity may intensify concentration gradients.…”
Section: Discussionsupporting
confidence: 83%
“…In large hillslopes with long flow paths, long MTTs can also drive weathering to equilibrium such that the control of VC diminishes. The Damköhler coefficient that explains CQ relationships of geogenic solutes (Ibarra et al., 2016; Maher & Chamberlain, 2014; Torres & Baronas, 2021; Wymore et al., 2017) indicate that long transit times lead to chemical equilibrium and chemostatic patterns. It implies that the dependence of weathering rates on VC and MTT will weaken as spatial scales increase.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported non‐monotonic behavior for Si (Torres & Baronas, 2021), sediments and nutrients (Underwood et al., 2017), and a variety of other solutes such as metals (Moatar et al., 2017; Zhi et al., 2019). The concentrations of DOC and NO 3 at the two study sites here decrease with depth and exhibit flushing CQ relationships.…”
Section: Discussionmentioning
confidence: 97%
“…The deeper subsurface contains reactive minerals such as carbonate (W‐9) as well as silicate and pyrite‐containing shale (Hafren). In addition, groundwater is typically much older than shallow water, which allows for longer reaction time with parent rocks (Maher, 2011; Torres & Baronas, 2021). In other words, prolonged exposure to parent rocks and longer transit times in groundwater give rise to higher concentrations of weathering‐derived solutes at depth and dilution CQ relationships.…”
Section: Discussionmentioning
confidence: 99%
“…As we infer above, this is likely the result of the distinct secondary phases dominating Ge uptake in each environment (aSi under the glaciers vs. Fe oxyhydroxides or aluminosilicate clays during the experiment and in natural nonglacial environments), which are in turn controlled by the distinct weathering regimes, and in particular the low temperatures, high rates of comminution, and relatively short water residence times in the subglacial environment. While the role that water transit times play in the dynamics of chemical weathering is poorly understood, it has very important implications for our understanding of the relationship between weathering and climate (e.g., Maher and Chamberlain, 2014;Li, 2019;Torres and Baronas, 2021). Therefore, the possibility that dissolved δ 74 Ge might be primarily controlled by rock-water interaction time and may help understand the kinetics of weathering is an intriguing prospect.…”
Section: Implications For Ge Isotope Behavior During Subglacial and Nmentioning
confidence: 99%